Perception of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement of authors publishing reviews in nursing journals: a cross-sectional online survey. Issue 4 (20th April 2019) - Tam, Wilson W S; Tang, Arthur; Woo, Brigitte; Goh, Shawn Y S
Abstract : Objective: The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement has been developed as a guideline for reporting systematic reviews and meta-analyses. Despite the prevalent use of the PRISMA statement in medicine and nursing, no studies have examined authors' perception of it. The purpose of this study is to explore the perception of the PRISMA statement of authors who published reviews, meta-analyses, or both in nursing journals. Design: Cross-sectional descriptive study. Methods: An online survey was conducted among authors who published reviews, meta-analyses, or both in nursing journals between 2011 and 2017. The selected authors' email addresses were extracted from the PUBMED database. A questionnaire—with a 10-point Likert scale (1— not important at all to 10— very important )—was developed to elicit their responses regarding their perception of not only the PRISMA statement as a whole, but also the individual items therein. Results: Invitations were sent to 1960 valid email addresses identified, with 230 responses (response rate: 11.7%) and 181 completed responses (completion rate: 9.2%). The average perceived importance of the PRISMA statement was 8.66 (SD=1.35), while the perceived importance for the individual items ranged from 7.74 to 9.32. Six items were rated significantly higher than the average rating, whereas one item was rated significantly lower. Conclusion: Most respondents perceived the PRISMA statement as important. Items related to information sources, selection, search-flow presentation, summary of findings, limitations and interpretation were deemed more important while the registration was deemed less so.